Development of pjbl-based teaching modules to improve critical and creative thinking skills - Yuliana, Ina; Toheri; Sukmaangara, Bayu (Pusat Studi Pengembangan Pembelajaran Matematika, 2025)
This study aims to develop a Project Based Learning (PjBL)-based teaching module to enhance students’ critical and creative thinking skills on the topic of the Pythagorean Theorem. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The module was validated by five experts, resulting a score of 0.71, categorized as very valid. The module was tested on 38 eighth-grade students at SMP Negeri 11 Cirebon. The effectiveness test showed a significant improvement in students’ critical and creative thinking abilities, with N-Gain scores of 0.56 and 0.57 respectively, both categorized as moderately effective. The Wilcoxon test showed a significance value of 0.000 for both skills, indicating a significant difference between pretest and posttest scores. Additionally, student responses to the module were highly positive, with an average score of 85.91%. Based on these results, the developed PjBL-based teaching module is considered feasible and effective for enhancing higher-order thinking skills in mathematics learning.